Penerapan Pembangkit Listrik Tenaga Surya Sebagai Energi Tempat Sampah Otomatis Berbasis IoT - Mohamad Fathur Rahman; Ibrahim Lammada (Jurnal Ilmiah Wahana Pendidikan, 2022)
Trash cans have a vital role in society, the presence of trash bins is an obligation to improve cleanliness in the community, but when the trash can is full sometimes the janitor is late to come and re-emptied the trash. To make it easier to provide information to cleaners, the author makes an Automatic Trash Can Based on the Internet Of Things Bot Telegram Using a Hybrid PV Grid System by utilizing two voltage sources, namely by using a solar panel equipped with a battery as a power supply source and using electricity from the State Electricity Company (PLN). ). This automatic trash can can be a solution to the problem of garbage piling up due to the delay of the cleaners to empty the trash, so that it pollutes the surrounding air.